PENGUKURAN e/m elektron MENGGUNAKAN TABUNG TELEVISI (TV) DAN KUMPARAN HELMHOLTZ - Elyakim N. S. Patty; Endiyas Waluyo; Liefson Jacobus (Jurnal Penelitian Pendidikan IPA, 2015)
The purpose of this research is to determine the comparison value between e/m of electrons in the use of CRO television tube and use to examine the quality of the experimental method that was is by comparing the experimental method from J. J. Thomson. This research regarded as an experimental method, conducted by measuring the different of light points on the screen television tube to get the radius of electron motion. The data interpreted into a graph to a quaeter radius of current on the coil magnetic field Helmohltz I (amperes). This graph is used to find e/m value of electron and the result is: